2021
DOI: 10.1007/s00268-021-06305-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental Views on the Non‐Operative Management of Simple Appendicitis in Children: Results of a Cross‐Sectional Survey

Abstract: Background To determine parental attitudes for the non‐operative management of simple appendicitis and determine willingness to participate in research evaluating different management options. Method Voluntary cross‐sectional survey of parents/guardians presenting to paediatric outpatient department. Likert scale of 0–10 (strongly disagree–strongly agree) was utilised, analysis by individual question responses. Results are presented as medians [IQR], paired t test, the Mann–Whitney U test and Kruskal–Wallis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…They hoped to remove the influence of pre-existing medical knowledge through this independent methodology, and found that a similar proportion of adults expressed a preference for non-operative treatment (49%) and for surgery (44%). In a recently reported study similar to ours, Ensor et al surveyed 311 parents attending an outpatient clinic at a specialist children’s hospital in Australia [ 19 ]. They also found that parents typically overestimated the risk of dying from perforated appendicitis, and found similar proportions preferring non-operative (52%) and surgical treatments (48%).…”
Section: Discussionmentioning
confidence: 96%
“…They hoped to remove the influence of pre-existing medical knowledge through this independent methodology, and found that a similar proportion of adults expressed a preference for non-operative treatment (49%) and for surgery (44%). In a recently reported study similar to ours, Ensor et al surveyed 311 parents attending an outpatient clinic at a specialist children’s hospital in Australia [ 19 ]. They also found that parents typically overestimated the risk of dying from perforated appendicitis, and found similar proportions preferring non-operative (52%) and surgical treatments (48%).…”
Section: Discussionmentioning
confidence: 96%
“…An earlier study found that 82% of respondents thought it was "likely" or "very likely" that the appendix would rupture if surgery were postponed, and 81% thought it would quickly lead to severe complications and death in univariate analysis, which contradicts our findings [ 14 ]. Another study in Australia found that most respondents (73%) thought appendicitis required immediate surgery, and 88% thought ruptured appendicitis was a life-threatening illness [ 15 ]. In our survey, over half of the participants agreed that appendicitis has a low fatality rate (approximately one in ten).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with another study, which found that two-thirds of respondents preferred surgical treatment, while 24% preferred non-operative care [ 16 ]. Furthermore, an earlier Australian investigation revealed that 52% (131/252) favored surgical management, and 48% (121/252) preferred antimicrobial treatment [ 15 ]. However, according to another survey conducted in the Netherlands, 49.2% favored antibiotic treatment for uncomplicated appendicitis, 44.5% preferred surgery, and 6.3% could not decide [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to allow patients to choose their treatment was made based on evidence from previous studies showing that families are often unwilling to allow their children to be randomly assigned to treatment. 24 , 25 Use of a nonrandomized choice design may be more reflective of typical clinical practice and likely led to an increase in enrollment, but it may have also affected the generalizability of the results by introducing treatment selection bias. In addition, complete follow-up was available for 89% of patients who elected nonoperative management, leading to the possibility that loss to follow-up may have affected the results.…”
Section: Discussionmentioning
confidence: 99%